Prussian blue decorated hydrogel particles for effective removal of cesium ion from aqueous media. (9th January 2020) - Moon, Seongjun; Jang, Sun Woo; Kim, Yurim; Gil, Manjae; Lee, Kyung Jin
Abstract: The Prussian blue (PB)-decorated magnetic hydrogel particles are prepared by physical crosslinking of poly (vinyl alcohol) and in-situ PB-decoration. The physical crosslinking of the hydrogel particle was induced by reductive reaction of the iron ions in basic solution. "Drop-wise method" and "emulsification methods" were used to control the size of the particle, resulting in hydrogel particles with millimeter and micrometer scale, respectively. The prepared particles have magneticity for easy harvesting after ion absorption. The efficiency of removing cesium ions using the particles is investigated depending on the size of particle. As the surface area increases in the micron-sized particle, the particle can increase the efficiency of removing cesium. In addition, the adsorption mechanism of the prepared particle is further studied using pseudo-first/second order reaction model. Graphical abstract: Image 1 Highlights: Prussian-blue decorated hydrogel micro particle is prepared. The particle has magnetic property and effective ability for cesium adsorption. The kinetics of cesium adsorption is studied based on pseudo-first model and pseudo-second model.